2016
DOI: 10.5032/jae.2016.03115
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Learning, Motivation, and Performance Strategies for Teaching and Coaching CDE Teams

Abstract: This intrinsic case study examined the case of students on CDE (Career Development Event)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…To do this, a review was conducted of outcomes SBAE teachers expect from CDE participation to construct potential philosophies of CDEs. Of note, this review found CDE outcomes anticipated by teachers are vast (Ball et al, 2016;Russell, Robinson, & Kelsey, 2009); however, three main themes of outcomes emerged: a) student development, b) classroom extension, and c) competition and achievement. The three themes, described below, were used to construct the philosophies of CDES included in the current study.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…To do this, a review was conducted of outcomes SBAE teachers expect from CDE participation to construct potential philosophies of CDEs. Of note, this review found CDE outcomes anticipated by teachers are vast (Ball et al, 2016;Russell, Robinson, & Kelsey, 2009); however, three main themes of outcomes emerged: a) student development, b) classroom extension, and c) competition and achievement. The three themes, described below, were used to construct the philosophies of CDES included in the current study.…”
Section: Introductionmentioning
confidence: 94%
“…When considering CDEs, SBAE teachers identify opportunities for student development as drivers of participation (Ball et al, 2016;Russell et al, 2009). As a primary goal of CDEs is to develop career readiness skills (National FFA, 2016), many SBAE teachers indicate development of careerspecific knowledge and skills is a motivating factor of participation (Ball et al, 2016;Russell et al, 2009). In a study by Russell et al (2009), one SBAE teacher stressed skills demonstrated in CDEs are "some of the skills that they [students] will carry right on into their colleges and careers" (p. 111).…”
Section: Student Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it is appropriate for the national organization to develop events and awards that stimulate instruction in emerging areas that reflect both current and future community, national and global workforce needs. (p. iv) Research applied to competitions in SBAE, particularly to CDEs, has measured the perceptions of students, of agricultural education teachers, of parents, and of administrators to examine perceived purpose and benefits, to explore coaching and recruitment strategies, and to assess students' motivations to participate (Ball, Bowling, & Bird, 2016;Croom, Moore, & Armbrister, 2009;Knobloch et al, 2016;Lundry, Ramsey, Edwards, & Robinson, 2015;Russell, Robinson, & Kelsey, 2009). An incomplete understanding of the intracurricular nature of FFA activities by the public, and perhaps even by the stakeholders involved in agricultural education, has clouded, or, in some instances, misrepresented the presumed educational value of such (Bell, 1985).…”
Section: Introductionmentioning
confidence: 99%